The Effect of Artificial Intelligence on Student Reading Interest in Indonesian History Lessons at SMA ST. Antonius Medan - Silalahi, Anggi Juwita; Aisyah, Siti; br. Barus, Afriani Etimanta; Sitompul, Boas Fernando; Handayani, Mutia (IJISTECH (International Journal of Information System and Technology), 2024)
Artificial intelligence is a technology designed to help humans with their work. This technology is sophisticated and as similar as possible to how humans work. Artificial intelligence now plays an important role in all areas of life, including education. The world of education and artificial intelligence is closely tied because of its effective and efficient nature in assisting teaching and learning activities. Not only teachers, but students are also increasingly using artificial intelligence to help solve problems and even do assignments. With the existence of artificial intelligence, students are increasingly facilitated in getting information about lessons, one of which is in history lessons. So it is not uncommon for students to prefer to find information through artificial intelligence applications rather than reading books. This study was conducted to measure how influential artificial intelligence is in reducing students' interest in reading.